Vishnu seated on Adishesha - 010 - Saurabh Saxena (2022)
Image courtesy : Saurabh Saxena - https://puratattva.in/ Vishnu is traditionally shown sleeping on Adishesha, except here the he is shown sitting on the mighty serpent.